Field Trip Learning Method to Improve the Ability of Writing Descriptive Paragraph in Elementary School Students - Hendratno; Yasin, Fajar Nur; Damayanti, Maryam Isnaini; Subrata, Heru; Nurul Istiq’faroh (Universitas Pendidikan Ganesha, 2023)
Students from elementary school are expected to have good language skills because language is the most critical human capital. Speaking is an act carried out by every human being in togetherness with other humans to communicate. Language as a means of communication can be in the form of spoken language or written language. This research aims to analyze the effectiveness of the field trip method on elementary school student's ability to write descriptive paragraphs. The research carried out in this research is quantitative research. The method used in the research was quasi-experimental with a nonequivalent research design (pretest and posttest) control group design. The research sample consisted of 62 students consisting of 31 class IIIA students as the control class and 31 class IIIB students as the experimental class. Data was collected using test sheets to determine student learning outcomes. The data analysis used was a t-test analysis with a significance level of 5%. The research results show significant effectiveness in the ability to write descriptive paragraphs. Field trips for elementary school children can be used to expand the information obtained in class, providing experience regarding existing realities. Thus, the field trip method is effectively used to learn to write descriptive paragraphs and can be a solution for teachers experiencing similar learning obstacles.